A case of generalized pustular psoriasis - V. A. Oklopkov; O. V. Pravdina; A. A. Chermoschentsev; T. V. Repina; E. I. Poleshuk; V. G. Gudoshnik; R. V. Gorodilov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article presents a clinical case of generalized pustular psoriasis. Complex therapy features for this rare and severe type of psoriasis are described.